2004
DOI: 10.1021/jp048923u
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigation of the Coordination of N2 Ligands to the Cluster Ni3

Abstract: Various structures of complexes of the cluster Ni3 with 3 to 12 N2 ligands were modeled with a gradient-corrected density functional method. The stability of different types of bonding was considered and the most stable structures of Ni3(N2) x complexes (x = 3−9, 12) were determined for neutral, cationic, and anionic systems. For the most stable structure of the neutral complex with three and six N2 ligands, we calculated average ligand binding energies of 116 and 98 kJ/mol, respectively; the binding energy p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 61 publications
1
12
1
Order By: Relevance
“…We also studied the dissociative adsorption of up to 6 H 2 molecules on different metal tetramers [43,44,48]. In addition, we considered molecular adsorption of one or more CO or N 2 molecules on selected nickel clusters [45,50]. The obtained results indeed showed that hydrogen impurity atoms on the clusters cause an extension of the interatomic distances in the metal moieties, bringing them close to the experimental values.…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…We also studied the dissociative adsorption of up to 6 H 2 molecules on different metal tetramers [43,44,48]. In addition, we considered molecular adsorption of one or more CO or N 2 molecules on selected nickel clusters [45,50]. The obtained results indeed showed that hydrogen impurity atoms on the clusters cause an extension of the interatomic distances in the metal moieties, bringing them close to the experimental values.…”
Section: Introductionmentioning
confidence: 77%
“…In particular, we modeled clusters containing up to 6 nickel atoms [35][36][37]45] as well as tetra-atomic clusters of palladium [39], iridium [33,40,41,47,48], and platinum [34,42], and hexa-atomic rhodium [38]. All these clusters were considered to interact with hydrogen atoms, while on some clusters we also modeled the coordination of C and O.…”
Section: Influence Of Atomic Impurities On Structure and Stability Ofmentioning
confidence: 99%
See 3 more Smart Citations